Mental health problems, health risk behaviors, and prevention: A qualitative interview study on perceptions and attitudes among elite male soccer players - Kvillemo, Pia; Nilsson, Anders; Strandberg, Anna K.; Björk, Karl; Elgán, Tobias H.; Gripenberg, Johanna (Frontiers in Public Health, 2023)
Background: The purpose of this study was to investigate the perception of mental health problems and health risk behaviors among Swedish male elite soccer players and their attitudes towards possible prevention strategies. Method: Twenty elite soccer players, aged 15–30 years, were recruited through purposive sampling and interviewed via a digital video calling platform. A semi-structured interview guide, encompassing questions about mental health problems, health risk behaviors among soccer teams, peer-relations, relations to coaches, and attitudes towards health risk behaviors, along with proposals for effective interventions, was employed. The interviews were transcribed verbatim and analyzed with qualitative content analysis. Results: The informants reported positive feelings in relation to playing soccer, good health, and few health risk behaviors. Risk factors included a large income, excessive free time, and the need for excitement. Stress and mental health problems were linked to performance pressure, social media, and injuries. Hesitation to talk openly about personal problems due to concerns about negative consequences and the "macho culture" was highlighted as barriers to admit and seek help for personal problems. Some statements indicated openness and the club’s efforts to destigmatize personal problems. Positive attitudes towards prevention and suggestions for various measures were prominent. Conclusion: Future research and implementation of interventions should focus on the prevention of health risk behaviors and alleviation of stress and performance pressure, as well as continue the efforts to destigmatize mental health problems and raise awareness among coaches of the importance of their communication and behavior for players’ mental health and performance. This could be achieved by developing strategic and systematic policy work, information, and dialogue among players and coaches, in addition to individual digital or face-to-face support, provided by professionals outside the soccer context.